1988
DOI: 10.1111/j.1465-7295.1988.tb01668.x
|View full text |Cite
|
Sign up to set email alerts
|

DOES SEX STILL MATTER? NEW EVIDENCE FROM THE 1980s

Abstract: Recent analyses of gender based salary differentials among University faculty have focused on colleges and universities which are quite different from those used in earlier (pre‐1975) studies. To facilitate comparisons with previous studies we examine gender earnings differentials during the 1983–84 academic year at Kent State University, a school similar to those studied in the pre‐1975 period. Our results suggest that after controlling for differentials in productivity‐related characteristics and market infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Rank has consistently been shown to be the single best predictor of salary (Osborne, 1990;Raymond, Sesnowitz, and Williams, 1988;Stacy, 1983). Stacy and Holland (1984) argue that given the typical differences in the proportions of males and females at each rank, ignoring rank more than doubles any apparent salary disparity.…”
Section: Rank (Rank)mentioning
confidence: 97%
See 4 more Smart Citations
“…Rank has consistently been shown to be the single best predictor of salary (Osborne, 1990;Raymond, Sesnowitz, and Williams, 1988;Stacy, 1983). Stacy and Holland (1984) argue that given the typical differences in the proportions of males and females at each rank, ignoring rank more than doubles any apparent salary disparity.…”
Section: Rank (Rank)mentioning
confidence: 97%
“…Previous research (Raymond, Sesnowitz, and Williams, 1988;Regan, 1990) suggested that individuals who either previously held administrative appointments other than department chair or school director (e.g., deans) or who initially joined the university with an administrative appointment as department chair would re-ceive higher levels of compensation due either to their administrative contributions to the university or external market forces extant at their hiring. Thus, ADMIN was coded 1 for those faculty who held a prior administrative appointment at BGSU other than department chair and for those individuals initially hired as department chairs or school directors.…”
Section: Administrative Experience (Admin)mentioning
confidence: 98%
See 3 more Smart Citations